Diindenopyrazines: Electron‐Deficient Arenes. Issue 39 (4th June 2021) - Brosius, Victor; Weigold, Svenja; Hippchen, Nikolai; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: The syntheses, properties and application of the air‐stable electron acceptors, diindenopyrazines 4 a –g are reported demonstrating the introduction of functional aryl groups in the 6‐ and 12‐positions. The targets are accessible on the hundred milligram to gram scale. The structure of the aryl groups in 4 a –g modulates their solubility, redox potentials and optical properties. The introduction of electron‐poor aryl groups to the electron‐poor diindenopyrazine backbone reduces the electron affinity to −4 eV, making the compounds attractive as n‐semiconductors. A simple organic field‐effect transistor of 4 e –without optimization– shows electron transport with a mobility of up to 0.037 cm 2  V −1  s −1 . Abstract : Electron poor, but rich in possibility : Electron‐deficient diindenopyrazines with different aryl substituents have been synthesized and characterized. The introduction of electron‐poor aryl groups reduces the electron affinity to −4 eV, thereby making the compounds attractive as n‐semiconductors. Tested in an organic field‐effect transistor, compound 4 e showed electron mobilities up to 0.037 cm 2  V −1  s −1 .